Secondary organic aerosol production from local emissions dominates the organic aerosol budget over Seoul, South Korea, during KORUS-AQ - B. A. Nault (Atmospheric Chemistry and Physics, 2018)
Organic aerosol (OA) is an important fraction of submicron aerosols. However, it is challenging to predict and attribute the specific organic compounds and sources that lead to observed OA loadings, largely due to contributions from secondary production. This is especially true for megacities surrounded by numerous regional sources that create an OA background. Here, we utilize in situ gas and aerosol observations collected on board the NASA DC-8 during the NASA–NIER KORUS-AQ (Korea–United States Air Quality) campaign to investigate the sources and hydrocarbon precursors that led to the secondary OA (SOA) production observed over Seoul. First, we investigate the contribution of transported OA to total loadings observed over Seoul by using observations over the Yellow Sea coupled to FLEXPART Lagrangian simulations. During KORUS-AQ, the average OA loading advected into Seoul was ∼1–3 µg sm−3. Second, taking this background into account, the dilution-corrected SOA concentration observed over Seoul was ∼140 µg<mspace linebreak="nobreak" width="0.125em"/>sm-3<mspace width="0.125em" linebreak="nobreak"/>ppmv-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="79pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="d198e7038e51b2f086bf28081c24baf7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-18-17769-2018-ie00001.svg" width="79pt" height="15pt" src="acp-18-17769-2018-ie00001.png"/></svg:svg> at 0.5 equivalent photochemical days. This value is at the high end of what has been observed in other megacities around the world (20–70 µg<mspace linebreak="nobreak" width="0.125em"/>sm-3<mspace width="0.125em" linebreak="nobreak"/>ppmv-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="79pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="39f2db729a3690304e1428c2bf74da1f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-18-17769-2018-ie00002.svg" width="79pt" height="15pt" src="acp-18-17769-2018-ie00002.png"/></svg:svg> at 0.5 equivalent days). For the average OA concentration observed over Seoul (13 µg sm−3), it is clear that production of SOA from locally emitted precursors is the major source in the region. The importance of local SOA production was supported by the following observations. (1) FLEXPART source contribution calculations indicate any hydrocarbons with a lifetime of less than 1 day, which are shown to dominate the observed SOA production, mainly originate from South Korea. (2) SOA correlated strongly with other secondary photochemical species, including short-lived species (formaldehyde, peroxy acetyl nitrate, sum of acyl peroxy nitrates, dihydroxytoluene, and nitrate aerosol). (3) Results from an airborne oxidation flow reactor (OFR), flown for the first time, show a factor of 4.5 increase in potential SOA concentrations over Seoul versus over the Yellow Sea, a region where background air masses that are advected into Seoul can be measured. (4) Box model simulations reproduce SOA observed over Seoul within 11 % on average and suggest that short-lived hydrocarbons (i.e., xylenes, trimethylbenzenes, and semi-volatile and intermediate-volatility compounds) were the main SOA precursors over Seoul. Toluene alone contributes 9 % of the modeled SOA over Seoul. Finally, along with these results, we use the metric ΔOA/ΔCO2 to examine the amount of OA produced per fuel consumed in a megacity, which shows less variability across the world than ΔOA∕ΔCO.